Thermal and stress-strain state of friction pairs in ventilated disc brakes of lightweight vehicles - O. Dykha; K. Holenko; J. Padgurskas; O. Babak (Проблеми трибології, 2023)
The work is dedicated to the thermal behavior and stress-strain state of ventilated disc brakes installed in the lightweight vehicles (scooters, electric bikes, ATVs, etc.) using ANSYS environment in various experiment modes. Modeling of the temperature distribution in the rotor (disc) and the corresponding brake pads is determined taking into account a number of factors and input parameters during the braking operation: the amount of rotation speed, the gap between the pads and the disc, the speed of load application, thermal expansion, etc. Numerical modeling of the transient thermal and the stress fields in the area of contact between the pads and the rotor is carried out by the method of sequential thermostructural connection of the intermediate calculation states of the brake model in the ANSYS Coupled Field Transient environment. For a comprehensive assessment of brake behavior, our research considers two load approaches: constant long-term (20 s) with an influence factor in the form of thermal expansion as a result of contact pair friction; linear load from the pads on the disс with a corresponding increase in pressure up to the moment when the rotation of the system is blocked. Our research presents an assessment of the rotor ventilation channels influence on the nature of the contact spot with the brake pads (open far-field contact, sliding contact, sticking contact, etc.). In addition, it is demonstrated that despite the linear increase in pads pressure on the rotor, the graphs of temperatures, volume (thermal expansion) and stresses are of parabolic character with a disproportionate increase in indicators. Such a result forces us to come to the conclusion that it is not possible to predict the behavior of the brakes based on the analysis during a short period of time of the experiment - conducting long-term analytical studies is extremely important in the case of brakes